2004
DOI: 10.1111/j.1399-3054.2004.00425.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate down‐regulates endogenous cytokinin levels in cotyledons of Cucurbita pepo (zucchini) seedlings

Abstract: Endogenous cytokinins (CK) were measured in Cucurbita pepo L. (zucchini) cotyledons after spraying 7‐day‐old seedlings with methyl jasmonate (MeJA) to examine whether the senescence‐promoting action of MeJA is associated with changes in metabolic regulation of CK levels. MeJA promoted senescence as estimated by the loss of chlorophyll and injury to chloroplast ultrastructure. This was already detected one day after treatment. The contents of physiologically active CKs determined by high‐performance liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The well-known ability of jasmonates to promote or enhance senescence upon exogenous application is often characterized by loss of chlorophyll, degradation of Rubisco and inhibition of its biosynthesis, decreased rates of transpiration and photosynthesis, up-regulation of several SAGs shown for different plants (Weidhase et al, 1987;Beltrano et al, 1998;Oh et al, 1996;Weaver et al, 1998;He et al, 2001He et al, , 2002. In addition, jasmonates can induce disorganization of the thylakoid membrane system of chloroplasts (Ananieva et al, 2004b). Jasmonates can also affect the functional activity of PSII (Woo et al, 2001;He et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The well-known ability of jasmonates to promote or enhance senescence upon exogenous application is often characterized by loss of chlorophyll, degradation of Rubisco and inhibition of its biosynthesis, decreased rates of transpiration and photosynthesis, up-regulation of several SAGs shown for different plants (Weidhase et al, 1987;Beltrano et al, 1998;Oh et al, 1996;Weaver et al, 1998;He et al, 2001He et al, , 2002. In addition, jasmonates can induce disorganization of the thylakoid membrane system of chloroplasts (Ananieva et al, 2004b). Jasmonates can also affect the functional activity of PSII (Woo et al, 2001;He et al, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…We have recently reported that the ability of MeJA to promote senescence in intact C. pepo (zucchini) cotyledons is at least partially due to down-regulation of endogenous CK levels and interconversions between their physiologically active and inactive forms (Ananieva et al, 2004b). Genes involved in JA biosynthesis were shown to be differentially up-regulated during leaf senescence of Arabidopsis resulting in a 4-fold increase in JA content in senescing leaves, thus supporting also a role of endogenous JA in Arabidopsis leaf senescence (He et al, 2002).…”
Section: Article In Pressmentioning
confidence: 99%
“…Similalry, terpenoid accumulation in developing xylem of Norway spruce stems was reported by MeJa treatment (Zeneli et al, 2006). A decrease in chlorophyll contents has been reported for Cucurbita pepo in response to MeJA treatment (Ananieva et al, 2004). Since chlorophyll is also derived from MEP pathway, MeJA down-regulated chlorophyll accumulation possibly by down-regulating genes of MEP pathway.…”
Section: Leaf Tissue Exhibits Highest Sgs Content and Expression Of Gmentioning
confidence: 94%
“…They can also induce the disorganization of the thylakoid membrane system in chloroplasts, affect the functional activity of PSII, decrease the rates of transpiration and photosynthesis, as well as cell up-regulates several SAGs shown in different plants (Ananieva et al 2004b;Beltrano et al 1998;He and Gan 2001;He et al 2002;Liu et al 2015;Weaver et al 1998;Weidhase et al 1987a, b;Woo et al 2001;Oh et al 1996). Jasmonates have been widely shown to be powerful promoters of leaf senescence (Chen and Kao 1998;Chou and Kao 1992;Hung and Kao 1996;Tsai et al 1996;Ueda and Kato 1981;Weidhase et al 1987a), but their participation in cotyledon senescence is still poorly understood (Ananieva et al 2004a(Ananieva et al , 2007. In the present study, we evaluate the effects of darkness and JAs on the senescence of I. nil cotyledons.…”
Section: Discussionmentioning
confidence: 99%